Impact of feed availability on growth performance and amino acid utilization of cobia (Rachycentron canadum) at elevated temperature - Le, Minh-Hoang; Espe, Marit; Conceição, Luís E. C.; Nguyen, Minh V.; Yúfera, Manuel; Engrola, Sofia; Jordal, Ann-Elise O.; Pham, Hung Q.; Rønnestad, Ivar (Frontiers in Aquaculture, 2024)
IntroductionThis study explored the effects of increased water temperatures and limited feeding on the growth, feed utilization, and nutrient retention in juvenile cobia (Rachycentron canadum).MethodsJuvenile cobia, approximately 5.0 g in body weight, were distributed across two temperature conditions: 34°C, to mimic a global warming scenario, and 30°C, the current local summer average, as controls. The setup included eighteen 200-liter tanks, with 20 fish per tank. Within each temperature regime, triplicate tanks received one of three feeding levels (55%, 75%, and 95% of satiation as determined at 30°C) over a six-week period.ResultsThe findings indicated that cobia exhibited the poorest growth performance at the elevated temperature (34°C) and the lowest feeding level (55%). These conditions also correlated with the lowest protein efficiency ratio and feed intake. The feed conversion ratio worsened with increased temperature and feeding levels, while protein production values decreased at higher temperatures. A lower feeding level caused a lower total lipid retention but led to increased retention of whole body essential amino acids.DiscussionAfter six weeks, a 24-hour post-prandial analysis showed selective retention of some amino acids in muscle and plasma, but significantly higher retention in the liver at the higher temperature. Only a few amino acids' retention was influenced by feeding level. These results suggest that temperature and feeding levels alter the prioritization of amino acid metabolism and retention, as well as the utilization of energy and substrates across different organs of the cobia.